Happiness and Satisfaction with Work Commute - Olsson, Lars E. (Springer Netherlands, 2012)
Research suggests that for many people happiness is being able to make the routines of everyday life work, such that positive feelings dominate over negative feelings resulting from daily hassles. In line with this, a survey of work commuters in the three largest urban areas of Sweden show that satisfaction with the work commute contributes to overall happiness. It is also found that feelings during the commutes are predominantly positive or neutral. Possible explanatory factors include desirable physical exercise from walking and biking, as well as that short commutes provide a buffer between the work and private spheres. For longer work commutes, social and entertainment activities either increase positive affects or counteract stress and boredom. Satisfaction with being employed in a recession may also spill over to positive experiences of work commutes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11205-012-0003-2) contains supplementary material, which is available to authorized users.